Codes to Process Seismic Data on Glacier from Quantification of seasonal and diurnal dynamics of subglacial channels using seismic observations on an Alpine Glacier' from Nanni et al., 2020 accepted in TC. - Ugo Nanni (Zenodo, 2020)
This contains the codes used to process SAC seismic data obtained on Argentière glacier from 2017 to 2019 and extract the associated seismic power to then investigate the subglacial hydrology properties. These codes are associated to the paper 'Quantification of seasonal and diurnal dynamics of subglacial channels using seismic observations on an Alpine Glacier' from Nanni et al., 2020 accepted in TC.